Effects of the Treatment Technology of Soybean on Volatile Flavor Compounds of Plant-based Compound Milk during Storage - Xue WANG; Youqiang YU; Xiaoyang ZHENG; Hongjiang MA; Shiwei LIU; Wenxin WANG; Fang ZHOU; Shenglin DUAN (Shipin gongye ke-ji)
To explore the effects of two industrial processes on the flavor of plant-based compound milk. Headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) combined with electronic nose and human sensory evaluation were used to analyze the differences of volatile flavor substances in the plant-based compound milk, that prepared by two soybean treatment technologies (oxygen separation grinding/enzyme inactivation with high temperature, grinding after enzyme inactivation) at different storage time (0, 90, 180 and 360 d). The results of human and electronic senses showed that the milk, flower, fruit and cereal flavors of plant-based compound milk 1# and 2# gradually increased during storage, and the peculiar smell gradually weakened. Furthermore, compared to plant-based compound milk 2#, the plant-based compound milk 1# displayed better flavor and smaller change ranges in five flavor dimensions. A total of 46 volatile flavor components were detected by HS-SPME-GC-MS, including 15 alcohols, 7 aldehydes, 3 acids, 7 esters, 6 ketones and 8 other components. The results of principal component analysis showed that hexanol, 1-tetradecanol, 1-hexanol, pyridine, ethyl caproate, ethyl palmitate, 2-heptanone, 2-octanone, 2-acetylthiazole were the key factors affecting the flavor change of plant-based composite milk 1#, while 2,3 butanediol, n-hexanal, maltol, benzaldehyde, ethyl acetate, 3-ethyl-2,5-dimethylpyrazine were the key factors affecting the flavor change of plant-based composite milk 2# during storage. In conclusion, the plant-based compound milk prepared by oxygen seperation grinding/enzyme inactivation with high temperature had more pronounced aroma, and exhibited smaller changes during storage, which proved that the treatment technology of oxygen separation grinding/enzyme inactivation with high temperature displayed more advantages in improving flavor and flavor stability of plant-based compound milk.